Friday

September 19, 2014

September 19, 2014

Posted by **John** on Wednesday, May 26, 2010 at 5:13pm.

I will assume you meant

g(x) = (x-3)^2

(f o g)(11) = f(g(11))

= f(64)

= 64-20

= 44

**Answer this Question**

**Related Questions**

Algebra-Reiny please explain this - Hi Reiny, I posted this problem earlier and ...

Chemistry - .50 - x / x = 3.20e-1 I need to solve for x. I was going to do .50 ...

Chemistry(Please check) - .50 - x / x = 3.20e-1 I need to solve for x. I was ...

algebra 2 - Reiny I do not understand where you got the numbers from in the ...

Algebra 1 (Reiny or Kuai) - Is the linear equation 3x - 2 = y in standard form...

Algebra 1 (Reiny or Kuai) - Is the linear equation 3x - 2 = y in standard form...

MATH (to Reiny) - I tried to simplify it with the second fraction by multiplying...

More algebra--please help! - Here are some more questions I'm having trouble ...

Algebra 1 (Reiny or Kuai) - Can a solution of a linear inequality lie on a ...

To Reiny - Reiny could you please check my Calculus post below, it says Calculus...